2013
DOI: 10.1002/hlca.201200085
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetric Study of Some Anti‐Chagas‐Active 1,4‐Dioxidoquinoxalin‐2‐yl Ketone Derivatives

Abstract: The electrochemical properties of 24 quinoxaline 1,4-di-N-oxide-2-ketone derivatives with varying degrees of anti-chagas activity were investigated in the aprotic solvent dimethylformamide (DMF) using cyclic voltammetry and first derivative cyclic voltammetry. For this group of compounds, the first reduction in DMF was either reversible or quasireversible and consistent with reduction of the N-oxide functionality to form the radical anion. The second reduction process for these compounds was found to be irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…For example, replacing the 7-hydrogen atom in compound 10 with the 7-methyl group in derivative 12 and the 7-methoxy group in 11 resulted in shifts in E 1/2 of -0.043 V and -0.076 V, respectively. The results of the present study agree with previous electrochemical studies dealing with the effects of structure on the reduction potentials of quinoxaline di-N-oxide derivatives, [46][47][48][50][51][52] and indicate that reduction is facilitated by a positive charge at the reaction site. [53] The influence of the substituent at R 2 , i.e.…”
Section: )supporting
confidence: 92%
See 3 more Smart Citations
“…For example, replacing the 7-hydrogen atom in compound 10 with the 7-methyl group in derivative 12 and the 7-methoxy group in 11 resulted in shifts in E 1/2 of -0.043 V and -0.076 V, respectively. The results of the present study agree with previous electrochemical studies dealing with the effects of structure on the reduction potentials of quinoxaline di-N-oxide derivatives, [46][47][48][50][51][52] and indicate that reduction is facilitated by a positive charge at the reaction site. [53] The influence of the substituent at R 2 , i.e.…”
Section: )supporting
confidence: 92%
“…[44,45] The electrochemical reductions of various quinoxaline di-N-oxide derivatives in aprotic solvent systems have been reported previously. [46][47][48][49][50][51][52]. In the current study, several voltammetric waves were observed during cyclic voltammetry of the quinoxaline di-N-oxide derivatives between -0.4 and -2.3 V. The first reduction process observed in the voltammograms may be attributed to reduction of the nitrone functionality, forming a radical anion (Figure 1).…”
Section: Electrochemistrymentioning
confidence: 54%
See 2 more Smart Citations
“…38,41,42 In order to shed some light on this subject, a study was conducted which involved the measuring of the reduction potentials of the N-oxide groups in different synthesized derivatives and selected analogs. The experimental goal of these studies was to determine the reduction potentials for two series of QDO: ketone 44 and ester 40 derivatives, in order to obtain evidence of the relationship between their electrochemical behaviour, their structure, and their anti-T. cruzi activity. The electrochemical properties of these compounds were studied using cyclic voltammetry and first derivative cyclic voltammetry in DMF with (Bu 4 N)ClO 4 as supporting electrolyte.…”
Section: Cyclic Voltammetry Studiesmentioning
confidence: 99%